2016
DOI: 10.1177/1545968316638444
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exercise Improves Memory Deficits via Restoration of Myelin and Microvessel Damage, and Enhancement of Neurogenesis in the Aged Gerbil Hippocampus After Ischemic Stroke

Abstract: These results suggest that long-term treadmill exercise after I-R can restore memory function through replacement of multiple damaged structures in the ischemic aged hippocampus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 61 publications
3
31
0
Order By: Relevance
“…Notably, we found that BBB integrity in I/R injury was also preserved by Sac-1004-induced stabilization of tight junction proteins and SMI-71 and GLUT-1. A decreased and dysregulated expression pattern of these proteins can be highly susceptible to brain damage during ischemic events [6163]. The Sac-1004-mediated restoration of these proteins can be an important step to preserve an intact brain region from ischemic damage.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we found that BBB integrity in I/R injury was also preserved by Sac-1004-induced stabilization of tight junction proteins and SMI-71 and GLUT-1. A decreased and dysregulated expression pattern of these proteins can be highly susceptible to brain damage during ischemic events [6163]. The Sac-1004-mediated restoration of these proteins can be an important step to preserve an intact brain region from ischemic damage.…”
Section: Discussionmentioning
confidence: 99%
“…Following the method described in our previous study (20), the gerbils were anesthetized with a mixture of 2.5% isoflurane (Baxter Healthcare Corporation, Deerfield, IL, USA) in 33% oxygen and 67% nitrous oxide. After a sagittal ventral midline incision, common carotid arteries were carefully separated from the respective vagal nerves and were occluded for 5 min using nontraumatic aneurysm clips (Yasargil FE 723K; Aesculap AG, Tuttlingen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Tissue processing was performed according to a previously published procedure (20). Briefly, animals (n=7/group) were anesthetized with sodium pentobarbital (40 mg/kg, i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Treadmill exercise promotes oligodendrocytes and, thus, myelination. In addition, the improvement of ischemia-induced myelin injury by long-term exercise is related to increased BdNF expression (28). Although the authors' previous studies (25,29,30) have focused on the neuroprotective effect of treadmill exercise in adult rats its neuroprotective effect on juvenile rats has not been explored.…”
Section: Treadmill Exercise Promotes Neurogenesis and Myelin Repair Vmentioning
confidence: 99%